Tobacco treatment incorporating contingency management, nicotine replacement therapy, and behavioral counseling for pregnant women who use substances: a feasibility trial - Jackson, Melissa A.; Brown, Amanda L.; Baker, Amanda L.; Bonevski, Billie; Haber, Paul; Bonomo, Yvonne; Blandthorn, Julie; Attia, John; Perry, Natasha; Barker, Daniel; Gould, Gillian S.; Dunlop, Adrian J. (Frontiers in Psychiatry, 2023)
Introduction Most pregnant women with substance use problems also smoke tobacco and few will stop during pregnancy. Tobacco treatment is often overlooked, with focus usually placed on other substance use. Additionally, few targeted effective treatments for this group exist. To address this, the feasibility of an intensive tobacco treatment incorporating contingency management (CM) that featured non-face-to-face delivery was examined. Methods A single-arm pre-post design feasibility trial was conducted in three antenatal services that support women who use substances in metropolitan Australia. Participants were aged over 15 years, less than 33-weeks’ gestation and smoked tobacco daily. They received: financial incentives for daily carbon monoxide verified smoking abstinence or reduction via an internet-based CM program, nicotine replacement therapy (NRT) posted to women and partners or household members who smoked, and telephone-delivered behavioural counselling from study enrolment till birth. Results Of 101 referrals, 46 women (46%) consented. Mean (SD) age was 31(6) years and gestation 22(6) weeks. Nineteen (41%) of those enrolled were retained to 12-weeks postpartum. Of 46 women, 32 (70%) utilised CM; 32 (70%) used NRT for 2 weeks; 23 (50%) attended 1 counselling session; and 15 (22%) received NRT for partners/household members. Fifteen (33%) were verified abstinent from tobacco at delivery after a median (IQR) period of abstinence of 65(36-128) days. All non-smokers at birth utilised NRT and financial incentives, 9/15 (60%) utilised counselling. Four (9%) were abstinent at 12-weeks postpartum. Median cigarettes smoked/day reduced from baseline to last contact (10(6-20) to 1(0-6) p=<0.001). Women who stopped smoking had more education (72% vs. 33% p=<0.02), completed more CO samples (median (IQR) 101(59-157) vs. 2(0-20) p=<0.001) and received higher incentives (median (IQR) $909($225-$1980) vs. $34($3-$64) p=<0.001). Intervention acceptability was rated favourably by participants (9-items rated 0-10 with scores considered favourable). Discussion This study demonstrated feasibility and acceptability of a consumer-informed, non-face-to-face intensive tobacco treatment, highlighting the potential of remotely delivered technology-based CM to reduce the health impact of tobacco smoking in high-priority populations. The intervention demonstrates scale-up potential. Future work should extend treatment into the postpartum period, utilising new technologies to enhance CM delivery and improve counselling provision and partner support.